A Compact Dual Band Elliptical Microstrip Antenna for Ku/K Band Satellite Applications - Mohamed Mahfoudh Harane; Hassan Ammor (Institute of Advanced Engineering and Science, 2018)
This paper presents an original elliptical microstrip patch antenna is proposed for Ku/K band satellite applications. The proposed antenna has a simple structure, small size with dimensions of about 10×12×1.58 mm³. The antenna has been designed and simulated on an FR4 substrate with dielectric constant 4.4 and thickness of 1.58 mm. The design is simulated by two different electromagnetic solvers. The results from the measured data show that the antenna has two resonant frequencies that define 2 bandwidths, defined by a return loss of less than -10 dB, and are: (14.44 GHz, 829 MHz) and (21.05 GHz, 5126 MHz),with the gain 5.59 dB and 5.048 dB respectively. The proposed antenna can be used in many applications such as in satellite, and wireless communications.